Detection of financial distress before and during the covid-19 pandemic: evidence from an automotive industry - Harjayanti, Diana Riyana; Akbar, Rifqi Raffi; Nurmasari, Ifa; Octariswan, Dony (Global Advances in Business Studies, 2023)
This study aims to analyze the effect of profit and cash flow in predicting financial distress in automotive sub-sector companies for the 2017-2021 period. This type of research is quantitative descriptive with the data analysis method used is descriptive statistical analysis using panel data which classical assumption test, statistic analyst by E-Views version 10 with a significance level of 0.05 (5 %). The results of this study indicate that profit affect financial distress as evidenced by the results of the t-test which shows that the significance value is 0.000 < 0.05. Cash flow also affects financial distress. This can be seen from the test results which show that the significance value is 0.021 < 0.05. The results of the F test show that profit and cash flow have a simultaneous effect on financial distress. This can be seen from the significance value of 0.000 <0.05 with a coefficient of determination of 0.929 meaning that financial distress as the dependent variable is influenced by profit and cash flow as independent variables of 92.9% and 7.1% is influenced by other variables.